Color Storytelling Sebagai Visual Narrative Pada Film Animasi The Red Turtle (International Forum of Researchers and Lecturers, 2023)
The Red Turtle is an animated film released in 2016. It was directed by Dutch-British animator Michall Dudok de Wit. The film is a co-production between Wild Bunch and Studio Ghibli. The Red Turtle tells of the struggle of a man stranded on an uninhabited island to survive until he finally finds new happiness on the island. The film